Faktor yang Berhubungan dengan Kekambuhan Asma pada Pasien Dewasa - Djamil, Achmad; Hermawan, Nur Sefa Arief; Febriani, F; Arisandi, William (Universitas Aisyah Pringsewu (UAP) Lampung, 2020)
In Indonesia, asthma is included in the top ten diseases that cause illness and death. Although the exact cause of asthma is still not known, there are several factors that cause asthma, namely genetic and environmental factors. According to data from the Bandar Lampung City Health Office in 2017 the puskesmas that has the highest number of asthma visits is the Sukabumi community health center, with an asthma visit rate of 477 with a new number of visits 191 and an old visit of 286 and the most asthma visit occurring at vulnerable ages 20-44 137 years. Asthma is a chronic inflammatory disease (inflammation) of the respiratory tract that is characterized by the presence of wheezing, coughing, and repeated congestion in the chest and arises mainly at night or early morning due to blockage of the respiratory tract. This disease is still a public health problem in almost all countries in the world, suffered by children to adults with mild to severe degrees of illness, even some cases can cause death. The purpose of this study was to determine the factors that connected with asthma recurrence in adult patients at the Public health center Sukabumi in Bandar Lampung in 2018. This type of research is analytic observational with a cross-sectional research design. The population in this study were all patients with asthma aged 20-44 years, amounting to 42 respondents. Sampling using a total sampling technique so that the number of samples equals the population. Data collection used secondary and primary data with questionnaire research instruments. Data analysis was done univariate and bivariate with the chi-square test. The results showed that the factors that connected with the recurrence of asthma were dust exposure (p-value 0.001 and OR 18), exposure to secondhand smoke (p-value 0.013 and OR 6.4), exposure to respiratory tract infections (p-value 0.016 and OR 6.171) and exposure to cold weather changes (p-value 0.035 and OR 4.857) which means that there is a statistically significant relationship while the factors that do not connect with asthma relapse are sports exposure (p-value 1,000) and stress exposure (p-value 0.798) which statistically they have no relationship. Based on the results of the study above, it is recommended that the puskesmas need to increase counseling regarding preventive procedures related to what factors can cause asthma recurrence.